Neonatal seizure identification on reduced channel EEG. Issue 4 (27th October 2012) - Kidokoro, Hiroyuki; Kubota, Tetsuo; Hayakawa, Masahiro; Kato, Yuichi; Okumura, Akihisa
Abstract : Using a standard digital EEG system, we conducted simulations to determine the optimal locations and numbers of electrodes for seizure detection in neonates with reduced-channel EEG monitoring. The results showed that C3–C4 should be selected for a one-channel recording, but two-channel seizure monitoring is recommended for increased accuracy.